2022
DOI: 10.1128/mbio.00395-22
|View full text |Cite
|
Sign up to set email alerts
|

Catabolic Ornithine Carbamoyltransferase Activity Facilitates Growth of Staphylococcus aureus in Defined Medium Lacking Glucose and Arginine

Abstract: Staphylococcus aureus can cause infection in virtually any niche of the human host, suggesting that it has significant metabolic versatility. Indeed, bioinformatic analysis suggests that it has the biosynthetic capability to synthesize all 20 amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 84 publications
(113 reference statements)
4
14
0
Order By: Relevance
“…These authors also showed that in the presence of glucose, and even in the absence of arginine, S. aureus behaves like an arginine auxotroph showing that absence of arginine alone is not enough to trigger arginine biosynthesis. The authors suggested that, during abscess infection, where active macrophages are found, arginine and glucose are depleted, thus activating arginine biosynthesis from proline (27). Our hypothesis is that incubation of SA at a fever-like temperature for 2 h triggers some physiological responses similar to those displayed after immune system activation even though glucose is present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also showed that in the presence of glucose, and even in the absence of arginine, S. aureus behaves like an arginine auxotroph showing that absence of arginine alone is not enough to trigger arginine biosynthesis. The authors suggested that, during abscess infection, where active macrophages are found, arginine and glucose are depleted, thus activating arginine biosynthesis from proline (27). Our hypothesis is that incubation of SA at a fever-like temperature for 2 h triggers some physiological responses similar to those displayed after immune system activation even though glucose is present.…”
Section: Resultsmentioning
confidence: 99%
“…2A). Reslane et al (2022) (27) reported that when glucose and arginine are absent, SA is a functional prototroph. These authors also showed that in the presence of glucose, and even in the absence of arginine, S. aureus behaves like an arginine auxotroph showing that absence of arginine alone is not enough to trigger arginine biosynthesis.…”
Section: Metabolic Reshaping Of S Aureus and P Aeruginosa After Expos...mentioning
confidence: 99%
“…Since arginine metabolism was implicated as having a role in antibiotic tolerance in both screens, we sought to better understand the role of arginine within S. aureus biofilms. S. aureus is unique in that it contains intact copies of the genes encoding all of the enzymes necessary to synthesize arginine from glutamate or proline, but is auxotrophic for arginine during planktonic growth (2932). Given its requirement for arginine during planktonic growth, we hypothesized that exogenous arginine was also required for growth in a biofilm.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of S. aureus to induce tolerance by restricting its own arginine synthesis pathway may explain a long-standing paradox-namely that wildtype S. aureus has fully functional arginine synthesis enzymes yet does not synthesize arginine under any in vitro conditions that have been tested thus far (31, 32). In line with other studies, S. aureus was unable to grow without arginine (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…While RelP and RelQ respond to stresses like cell-wall-targeting antibiotics and alterations in pH ( 10 ), Rel synthesizes (p)ppGpp during amino acid depletion, leading to large transcriptional changes, including the downregulation of protein synthesis machinery and upregulation of amino acid transport and metabolism genes ( 4 ). As S. aureus is a conditional auxotroph for a number of amino acids ( 11 , 12 ), this regulation of amino acid uptake is essential for survival in starved conditions ( 9 ). In proteobacteria, (p)ppGpp modulates changes in transcription of these genes by binding to two sites around the β′ subunit of the RNA polymerase, leading to altered expression of roughly a third of the genome ( 13 ).…”
Section: Introductionmentioning
confidence: 99%